2022
DOI: 10.3389/fpls.2022.955628
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Characterization of a β-Glucosidase Gene to Produce Platycodin D in Platycodon grandiflorus

Abstract: Platycodin D (PD) is a deglycosylated triterpene saponin with much higher pharmacological activity than glycosylated platycoside E (PE). Extensive studies in vitro showed that the transformation of platycoside E to platycodin D can be achieved using β-glucosidase extracted from several bacteria. However, whether similar enzymes in Platycodon grandiflorus could convert platycoside E to platycodin D, as well as the molecular mechanism underlying the deglycosylation process of platycodon E, remain unclear. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…About 89 known saponins were extracted from Platycodon grandi orus. The glycosyl ligands in Platycodon saponins are mainly composed of D-glucose, L-rhamnose, L-arabinose, D-xylose, and D-apposite and their derivatives [9,10,11]. It has been reported that Platycodon grandi orus saponin can attenuate the speci city of NF-κB and STAT1 by inhibiting Nrf2/ARE-mediated heme oxygenase-1 simultaneously [12].…”
Section: Introductionmentioning
confidence: 99%
“…About 89 known saponins were extracted from Platycodon grandi orus. The glycosyl ligands in Platycodon saponins are mainly composed of D-glucose, L-rhamnose, L-arabinose, D-xylose, and D-apposite and their derivatives [9,10,11]. It has been reported that Platycodon grandi orus saponin can attenuate the speci city of NF-κB and STAT1 by inhibiting Nrf2/ARE-mediated heme oxygenase-1 simultaneously [12].…”
Section: Introductionmentioning
confidence: 99%